Environmental microbial reservoir influences the bacterial communities associated with Hydra oligactis - Jay Bathia; Máté Miklós; István Gyulai; Sebastian Fraune; Jácint Tökölyi (Scientific Reports)
Abstract The objective to study the influence of microbiome on host fitness is frequently constrained by spatial and temporal variability of microbial communities. In particular, the environment serves as a dynamic reservoir of microbes that provides potential colonizers for animal microbiomes. In this study, we analyzed the microbiome of Hydra oligactis and corresponding water samples from 15 Hungarian lakes to reveal the contribution of environmental microbiota on host microbiome. Correlation analyses and neutral modeling revealed that differences in Hydra microbiota are associated with differences in environmental microbiota. To further investigate the influence of environmental bacterial community on the host microbiome, field-collected Hydra polyps from three populations were cultured in native water or foreign water. Our results show that lake water bacteria significantly contribute to Hydra microbial communities, but the compositional profile remained stable when cultured in different water sources. Longitudinal analysis of the in vitro experiment revealed a site-specific change in microbiome that correlated with the source water quality. Taken together, our findings demonstrate that while freshwater serves as a critical microbial reservoir, Hydra microbial communities exhibit remarkable resilience to environmental changes maintaining stability despite potential invasion. This dual approach highlights the complex interplay between environmental reservoirs and host microbiome integrity.